2021
DOI: 10.1080/23311932.2021.1918878
|View full text |Cite
|
Sign up to set email alerts
|

Structure conduct and performance of dairy market in Ada’a Berga district, Ethiopia

Abstract: The aim of this article was to investigate SCP of milk and butter market in Ada'a Berga District using SCP model. Primary data collected from randomly selected 123 smallholder farmers, 48 traders and 30 consumers were used to calculate the gross margin, concentration ratio(CR), regulation of market entry and exit and market conduct. The CR results showed that top four milk traders controlled 78.8% and 89.54% of the total volume of milk sold in Ada'a Berga and Holeta, respectively, and 61.29% and 63.46% butter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The performance of vegetable seed companies considered the most important factor was distribution depth. Ordofa et al [14] showed that dairy market in Ethiopia was strong oligopolistic type. The main barriers to entry milk and butter trade were corruption, political equality, education, market capital and transparency respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of vegetable seed companies considered the most important factor was distribution depth. Ordofa et al [14] showed that dairy market in Ethiopia was strong oligopolistic type. The main barriers to entry milk and butter trade were corruption, political equality, education, market capital and transparency respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies showed that the decision of milk farmers on their choice of milk market outlet is influenced by the characteristics related to membership in a cooperative, form of payment, volume of milk produced, level of education and marketing costs (Jaiswal et al, 2016), being in rural areas, breed type, separate milking place, supply of hay (Ketema et al, 2016), transaction costs and socio-economic variables such as sex, dairy farming experience, dairy cooperative membership, number of milking cow owned, frequency of extension contact, non-farm income (Ayyano et al, 2020), milk buyers' related factors such as purchase frequency and quantity purchased (Berem et al, 2015), institutional factors such as access to credit and financial strength (Innocent et al, 2018), characteristics related to the seller (reputation, desire to control channel) and market information (Ishaq et al, 2017;Singh, 2018;Zegeyesh et al, 2017). Past studies on the dairy market show more attention given to participation of producers in the dairy market and marketing efficiency of the chain (Ordofa et al, 2021). However, limited work was done on the choice pattern of farmers when it comes to channel choice and the factors influencing those choices regarding outlet of milk market.…”
Section: Introductionmentioning
confidence: 99%
“…Competition or imbalance does not occur among members in marketing if there is coordination and supervision of the stakeholders, particularly the government . According to Ordofa, Zemedu and Tegegne, (2021) and , to keep marketing sustainable, it is necessary to increase the involvement of some institutions that can support the financial strengthening and marketing performance.…”
Section: Introductionmentioning
confidence: 99%